Proposal of New Emulsion Systems Containing Hydroxypropylmethylcellulose as a Viscosity Modifier and Diacylglycerols from Mutton Tallow and Hemp Seed Oil - Małgorzata Kowalska; Magdalena Woźniak (Applied Sciences, 2023)
The purpose of this study was to analyze the stability of new emulsions prepared on the basis of modified fats with varying amounts of hydroxypropylmethylcellulose. Selected techniques for evaluating the stability of emulsion systems, such as Turbiscan analysis, and the evaluation of microstructure, texture, particle size and viscosity were used. The evaluation of the above-mentioned studied parameters allowed us to indicate differentiated stability and their properties. The most desired results in terms of stability evaluation were determined for the emulsion prepared on the basis of modified mutton tallow with hemp seed oil in a ratio 3:1 (by weight) containing 0.6% (by weight) of hydroxypropylmethylcellulose. In addition, as the hemp seed oil content in the interesterified fat phase increased, a decrease in the stability of the emulsion systems was noted. Mentioned emulsions were characterized with the lowest value of TSI. Moreover, for those emulsions, the smallest increment in the droplet diameter values of systems after 31 days was recorded. The prepared model formulation can serve as a starting material for new emulsion chemical, cosmetic or food systems.